Pendampingan Pengetahuan tentang Pernikahan Anak Usia Dini - Sofafia, Efa; Dian Safitri, Ayu; Anggraeni, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Early childhood marriage is a phenomenon that often occurs in various regions, including the northern coastal areas. Many factors trigger early child marriage, including economic, educational, and socio-cultural factors. Through the Service-Learning method, assisting parents and teenagers regarding knowledge of early childhood marriage is essential. Karang Anyar village, Tirto, and Depok village, Siwalan, are locations for mentoring activities. This mentoring activity provides education regarding child marriage at an early age, as well as the impact it has on children. The high rates of divorce, violence, and health problems that often occur in mentoring locations cannot be separated from the effects of early child marriage. Therefore, this assistance is carried out to reduce and prevent early child marriage.